PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN MODEL PEMBELAJARAN PICTURE AND PICTURE DI KELAS V SDN 18 AIR TAWAR SELATAN KOTA PADANG - Hasibuan, Amelia Wardana; Chandra, Chandra; Habibi, M; Safitri, Serly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of narrative writing skills among fifth-grade students at SDN 18 Air Tawar Selatan in Padang, which was identified through field observations. The difficulties experienced included an inability to compose narrative texts in a coherent manner, unclear story elements, imperfect narrative text structure, and errors in language usage and spelling. To address these issues, this study aims to improve narrative writing skills by implementing the Picture and Picture learning model. The research design used is Classroom Action Research (CAR) with a qualitative and quantitative approach, conducted in two cycles encompassing the stages of planning, implementation, observation, and reflection. Data were collected through test and non-test techniques, with the research subjects consisting of the homeroom teacher and 15 fifth-grade students at SDN 18 Air Tawar Selatan. The research results indicate a significant improvement in various aspects, including the RPPM, which increased from 89,29% (B) to 96,43% (SB), teacher activity, which increased from 87,5% (B) to 97,92% (SB), and student activity, which also increased from 87,5% (B) to 97,92% (SB). Additionally, students’ narrative writing skills improved from 79,07% (C) to 88,75% (B). Based on these findings, it can be concluded that the Picture and Picture learning model is effective in improving narrative writing skills among fifth-grade students at SDN 18 Air Tawar Selatan in Padang City.